On the measurement of polarisation: a questionnaire study - Yoram Amiel; Frank A. Cowell; Xavier Ramos (Institute for the Study of Labor (IZA), 2007)
Starting from the axiomatisation of polarisation contained in Esteban and Ray (1994) and Chakravarty and Majumdar (2001) we investigate whether people's perceptions of income polarisation is consistent with the key axioms. This is carried out using a questionnaire-experimental approach that combines both paper questionnaires and on-line interactive techniques. The responses suggest that important axioms which serve to differentiate polarisation from inequality e.g. increased bipolarization as well as other distinctive features of polarisation, i.e. the non-monotonous behaviour attributed to polarisation, are not widely accepted.
urn:nbn:de:101:1-20080410318
Keywords: 330; Einkommensverteilung; Disparitätsmaß; Meinung; Soziale Ungleichheit; Großbritannien